European Union’s Migration Policies: Strengthening Europe's Security and Stability, a Case of the Western Balkan Route - Husnurrahman, Fadli; Tairas, David Ronald (Indonesian Journal of Advanced Research, 2026)
This research aims to evaluate the European Union's policy to improve the security and stability of the Western Balkans region from illegal immigrants. The Western Balkans region is crucial to the European Union's policy in managing migration issues. A significant increase in the 2021-2022 period on the western Balkan route attracted the attention of the European Union and made it a priority in order to maintain security in the European Region. This research was analyzed based on European Union policies maintaining the security and stability of the Western Balkans. This study uses a descriptive qualitative method using a literature study. Findings of this study explain that at least there is an action plan formulated by the European Union in December 2022, which sets out a series of measures to strengthen European Union support to states facing increasing migration pressure along the Western Balkan route.